Normalizing the Bender Visual-Motor Gestalt Test for 4 to 7 Years Old Children of Tehran, Iran - Siamak Tahmasebi; Saman Mafakheri Bashmaq; Atefe Emad-; Rahele Rezaei (University of Social Welfare and Rehabilitation Sciences, 2016)
Objective Bender-Gestalt is one of the well-known neurocognitive tests designed by Lorta Bender to evaluate perceptual-motor development level in children. Besides its principle application in evaluation of cerebral damage, Bender test has other important applications, such as evaluating children for entering school, anticipating educational progress, diagnosing children with reading and learning disorders, studying growth retardation, as well as a nonverbal intelligence test to evaluate children’s reading readiness to enroll in elementary school. Because of the importance of this test in many diagnostics aspects, it is necessary to prepare a normalized form of this test. In this study, we tried to provide this form in a more comprehensive and updated form compared to previous studies. Materials & Methods This is a descriptive-analytic research. The study population comprised all preschool children in Tehran. In this research, we surveyed 523 (271 boys and 252 girls) preschool children in 3 groups of 4-5 years old (200 children, 95 boys and 105 girls), 5-6 years old (199 children, 112 boys and 87 girls), and 6-7 years old (124 children, 64 boys and 60 girls) who were selected by cluster sampling method from some preschools centers in south, north, and center of Tehran during the spring of 2012. The inclusion criteria were having normal intelligence quotient and being in the range of preschool age. Obtained protocols were numbered on the basis of expanded Koppitz scoring system, and finally were analyzed using the Chi-squared test. Results Data analysis for 4-5 years old group revealed the result of M(SD) as 14.75(1.82). The most frequent errors belonged to distortion in plans A, 7, and then 8. Also, the least frequent errors belonged to linear drawing of plans 3 and 6. With regard to misproportion error in plan A and repetition error in plan 2, girls made significantly less errors than boys, while with regard to spin errors of plan 7 and misproportion in plan 7, boys got the higher scores. In 5-6 years old group of children, M(SD) was 9.67(4.38). Also, the most frequent errors belonged to distortion in plans 8 and A. Furthermore, the least frequent errors belonged to linear drawing in plan 3, distortion in plan 7, and isproportion of components in plan 5. With regard to inappropriate composition and linear drawing of plan 5, boys made significant higher errors than girls. For children of 6-7 years old, M(SD) was 8.14(4.17). The most common errors in drawing belonged to first distortion errors in plans A and 8, and then spins in plans 7 and 3, and lastly to misproportion in plan 7. The least frequent errors belonged to linear drawing of plans 5 and 3, spin in plans 8 and 1, and finally distortion in plan 1. Male gender was effective in committing errors of wrong composition of plans A and 3, spin in plan 1, figure distortion in plans 6 and 7, also female gender in errors of wrong composition of plan 2, spin in plans 2 and 8. Conclusion Consistent with Koppit’z maturational hypothesis and previous studies (Iranian and foreign), our results showed visual-motor improvement of perceptual performance with increasing age. In conclusion, koppitz scoring system is applicable to Iranian children protocols.